Stock Valuation and Learning about Profitability - Pástor, Ľuboš; Pietro, Veronesi (Journal of Finance, 2003)
Abstract We develop a simple approach to valuing stocks in the presence of learning about average profitability. The market‐to‐book ratio (M/B) increases with uncertainty about average profitability, especially for firms that pay no dividends. M/B is predicted to decline over a firm's lifetime due to learning, with steeper decline when the firm is young. These predictions are confirmed empirically. Data also support the predictions that younger stocks and stocks that pay no dividends have more volatile returns. Firm profitability has become more volatile recently, helping explain the puzzling increase in average idiosyncratic return volatility observed over the past few decades.